Breastfeeding Beyond Two Years: Challenging Traditional Norms and Promoting Child Health in Coron, Palawan - Bagatela, Mary Fearn; Acosta, Roy Albert (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the experiences of mothers in Coron, Palawan who practiced extended breastfeeding beyond two years, focusing on their socio-demographic characteristics, social norms and cultural beliefs, breastfeeding practices, perceived benefits and challenges, maternal confidence, and advocacy needs. The study was anchored on an integrated framework combining Maternal Role Attainment Theory, Social Cognitive Theory, Cultural Dimensions Theory, and the Input-Process-Output paradigm. A mixed-methods descriptive design with a phenomenological orientation was used. Fourteen mothers with direct experience of extended breastfeeding were selected through purposive sampling. Data were gathered using a structured questionnaire adapted from an existing extended breastfeeding instrument, supplemented by one-on-one in-depth interviews. Quantitative data were analyzed using frequency, percentage, and weighted mean, while qualitative data were examined through thematic analysis. Findings showed that extended breastfeeding was shaped by maternal maturity, education, caregiving experience, family support, cultural expectations, healthcare guidance, and personal conviction. Mothers reported strong confidence and viewed the practice as beneficial for emotional bonding, child health, comfort, convenience, and cost-effectiveness. However, they also experienced fatigue, time demands, stigma, pressure to wean, misconceptions, and inconsistent professional support. The study concluded that extended breastfeeding is a multidimensional maternal and child health practice influenced by the interaction of individual agency, family and community responses, cultural context, and health system support. It recommends culturally sensitive health education, breastfeeding-friendly spaces, family and community support groups, stronger nursing-led counseling, policy integration, and broader future studies. The study aligns with SDG 3, SDG 4, SDG 5, SDG 8, and SDG 17 by supporting maternal and child health, health education, maternal autonomy, workplace support, and multi-sector collaboration. Its sustainability impact lies in strengthening public health, community support, socio-cultural awareness, gender-responsive care, and local health governance for extended breastfeeding.
Keywords: Advocacy Strategies; Breastfeeding Practices; Cultural Beliefs; Extended Breastfeeding; Maternal Confidence; Maternal Experiences; Social Norms